SUBTITUSI TEPUNG KETAN DENGAN RUMPUT LAUT (Eucheuma cottonii) PADA PEMBUATAN ENGKAK KETAN - Eka Ardiansyah; Susi Lestari; Siti Hanggita (Universitas Sriwijaya, 2014)
The objective of this research was to determine the effect of substitution of glutinous rice flour with seaweed for proximate, physic, sensory and microbiology. The research was conducted in March and April 2014 in Laboratory of Fisheries Technology and Laboratory of Bioprocess, Chemical Engineering Department, Sriwijaya University, Indralaya. This research used non factorial complete randomized design with four treatments and repeated twice. Glutinous rice flour was substituted with different concentration of seaweed A1 (12.5%), A2 (25%), A3 (37.5%), A4 (50%). The parameters observed were proximate analysis (water content), texture analysis, sensory (colour, texture and taste) and microbiology test. The results showed that substitution of glutinous rice flour with seaweed was not significant on hardness and water content. Based on analysis, the composition of the value obtained around 23.83-29.83% water content and 184.6-349.34 gf hardness analysis. Hedonic test was significant on colour and taste but not significant on texture. Microbiology test showed that engkak ketan is safe for eat on H0